The application of enzymatic fermented soybean effectively regulates associated microbial communities in tea soil and positively affects lipid metabolites in tea new shoots - Zhang, Shuning; Sun, Litao; Shi, Yujie; Song, Yujie; Wang, Yu; Fan, Kai; Zong, Rui; Li, Yusheng; Wang, Linjun; Bi, Caihong; Ding, Zhaotang (Frontiers in Microbiology, 2022)
Compared with traditional organic fertilizer, fermented soybean is a better fertilizer resource in tea plantation. However, the effects of fermented soybean on soil microbial communities, soil metabolites and metabolites in tea new shoots have not been systematically demonstrated, and their interactions have never been studied. Here, we firstly developed a special fertilizer using enzymatic fermented soybean, and then studied the changes of tea soils and tea new shoots after natural fermented soybean fertilization (NFS) and enzymatic soybean fertilization (EFS), and finally carried out a comprehensive correlative analysis. The results showed that Enterobacter and Bacillus were significantly enriched in enzyme fermented soybean, and palmitic acid, oleamide and 11-oxohexadecanoic acid were released during enzymatic fermentation, indicating soybean fertilizers were degraded rapidly and thoroughly due to the addition of enzymes. After fertilization, soil microbial communities established close relationships with soil metabolites. In soils, bacterial genus (Glutamicibacter, Streptomyces) and fungal genus (Candida, Actinomucor) presented high abundances in EFS, which resulted in the up-regulation of soil carbohydrate and lipid (D-Mannitol, D-Sorbitol, 9,12-Octadecadienoic acid and (Z)-13-Docosenoic acid. Besides, enzymatic soybean fertilization could accelerate soil phosphorus cycling and enrich growth-promoting microbes, therein, the relative abundance of Pseudomonas and Chitinophaga was significantly correlated with soil available phosphorus. In tea new shoots, triacylglycerols, diacylglycerols and ceramides showed a significant up-regulation trend in EFS, which were mainly affected by soil fungal communities. This study found that the application of fermented soybean had great potential contributions to improve tea quality and could open an effective way to cultivate high-quality tea by using soybean as high-grade fertilizer. In addition, this study expanded the understanding of complex soil-microbe-plant interactions in tea plants, which lay a theoretical foundation and technological support for the directional regulation of tea quality.